PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS MASALAH UNTUK MATERI HIMPUNAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMPN 3 LUBUK BASUNG - Ade, Fatimah - (STKIP PGRI Sumbar, 2014)
This research was conducted as the textbooks provided could not help the students much in the learning process, so that learning materials designed directly by the teacher was needed. These materials should enable the students to learn independently, and they should be easy to be understood, have communicative language and are effective to improve the studentsâ problem solving ability. Therefore, a problem-based Student Worksheet for teaching assemblage topic was developed. This research was aimed at developing problem-based Student Worksheet which was valid and practical. This was a developmental research which used 4-D model consisting of defining, designing, developing, and disseminating. The defining phase consisted of syllabus and Lesson Plan analysis, textbook analysis, the studentsâ characteristics analysis, and interview done to the teacher and the students. In the designing phase, the problem-based Student Worksheet was developed. In the developing phase, the Student Worksheet was tested its validity and practicality. The result of the validity test showed that the Student Worksheet developed was valid (3,63) and the result of the practicality indicated that Student Worksheet was very practical (84%)